Manajemen Pemasaran Bank Syariah Berbasis Tekhnology Revolusi Industry 4.0 - Irawan, Dedeng; Sugianto; Siregar, Saparuddin (Ikatan Da'i Indonesia, 2022)
Marketing of Islamic banks must have an economic construction 4.0, which is a fundamental change in the way of human life and work processes, where advances in information technology can integrate in the world of life with digital which can have an impact on scientific disciplines. This research is expected to add to the scientific treasures in the field of Islamic banking, especially those related to Islamic Banking issues in Facing Economic Construction 4.0 Reviewed Through SWOT Analysis which can be used as reference material for further researchers who conduct similar research. The formulation of the problem in this study is how the strategy of Islamic banking in dealing with economic construction 4.0 is reviewed through a SWOT analysis, and also to find out what are the obstacles of Islamic banking in facing economic construction 4.0 through a SWOT analysis. This research is a qualitative research with a qualitative research model with a case study approach model, which is a research approach that tries to explore real life through detailed and in-depth data collection involving various sources of information, either in the form of interviews, document observations or reports by describing objects from research case. The research results obtained are that Islamic banks must have a strategy to face the 4.0 industrial revolution, which researchers then analyze using SWOT